How Do University Students’ Web Search Behavior, Website Characteristics, and the Interaction of Both Influence Students’ Critical Online Reasoning? - Nagel, Marie-Theres; Schäfer, Svenja; Zlatkin-Troitschanskaia, Olga; Schemer, Christian; Maurer, Marcus; Molerov, Dimitri; Schmidt, Susanne; Brückner, Sebastian (Frontiers in Education, 2020)
The Internet has become one of the main sources of information for university students’ learning. Since anyone can disseminate content online, however, the Internet is full of irrelevant, biased, or even false information. Thus, students’ ability to use online information in a critical-reflective manner is of crucial importance. In our study, we used a framework for the assessment of students’ critical online reasoning (COR) to measure university students’ ability to critically use information from online sources and to reason on contentious issues based on online information. In addition to analyzing students’ COR by evaluating their open-ended short answers, we also investigated the students’ web search behavior and the quality of the websites they visited and used during this assessment. We analyzed both the number and type of websites as well as the quality of the information these websites provide. Finally, we investigated to what extent students’ web search behavior as well as the quality of the used website contents are related to higher task performance. To investigate this question, we used five computer-based performance tasks and asked 160 students from two German universities to perform a time-restricted open web search to respond to the open-ended questions presented in the tasks. The written responses were evaluated by two independent human raters. To analyze the students’ browsing history, we developed a coding manual and conducted a quantitative content analysis for a subsample of 50 students. The number of visited webpages per participant per task ranged from 1 to 9. Concerning the type of website, the participants relied especially on established news sites and Wikipedia. For instance, we found that the number of visited websites and the critical discussion of sources provided on the websites correlated positively with students’ scores. The identified relationships between students’ web search behavior, their performance in the CORA tasks, and the qualitative website characteristics are presented and critically discussed in terms of limitations of this study and implications for further research.